2022
DOI: 10.32615/bp.2022.008
|View full text |Cite
|
Sign up to set email alerts
|

24-epibrassinolide improved chilled tomato photosyntheticperformance by stabilizing electron transport chain and function of photosystem II

Abstract: Abbreviations: ABS/CS -absorption flux per CS; ABS/RC -absorption flux (exciting PS II antenna of Chl a molecules) per RC; AQY -apparent quantum yield; BRs -brassinosteroids; CEF -cyclic electron transport around PS I; ci -intercellular CO2 concentration; CS -cros section; E -transpiration rate; EBR -24-epibrassinolide; ETo/CS -electron transport flux per CS; ETo/RC -electron transport flux (further than QA -) per RC; ETR -electron transport rate; Fm -maximal fluorescence yield; Fo -minimal fluorescence yield;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Later, with the onset of cold weather, the efficiency of the acceptor side of PS II and then the donor side of PS II decreased as a result of photoinhibition and photooxidative stress. In previous studies, cold stress was previously shown to inhibit linear electron transport, whereas cyclic electron transport around PS I was enhanced, which contributes to the adaptive biochemical changes that occur as a result of walking stress [ 40 ]. The general change in the photosynthetic activity of leaves and the accumulation of protector substances (sugars) in oat leaves are in good agreement with the decrease in the reflection index (PRI), which in turn can serve as a good indicator of possible rearrangements in the photochemical processes and biochemical composition of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Later, with the onset of cold weather, the efficiency of the acceptor side of PS II and then the donor side of PS II decreased as a result of photoinhibition and photooxidative stress. In previous studies, cold stress was previously shown to inhibit linear electron transport, whereas cyclic electron transport around PS I was enhanced, which contributes to the adaptive biochemical changes that occur as a result of walking stress [ 40 ]. The general change in the photosynthetic activity of leaves and the accumulation of protector substances (sugars) in oat leaves are in good agreement with the decrease in the reflection index (PRI), which in turn can serve as a good indicator of possible rearrangements in the photochemical processes and biochemical composition of leaves.…”
Section: Discussionmentioning
confidence: 99%